Embedding external referencing of standards into higher education: collaborative relationships are the key - Sefcik, Lesley; Bedford, S.; Czech, P.; Smith, J.; Yorke, J. (Routledger, 2017)
External referencing of assessment and students’ achievement standards is a growing priority area within higher education, which is being pressured by government requirements to evidence outcome attainment. External referencing benefits stakeholders connected to higher education by helping to assure that assessments and standards within courses are appropriate and comparable among institutions. External referencing takes many forms, which have different resourcing requirements, outcomes, and operational strengths and challenges. This paper describes the External Referencing of Standards (ERoS) approach developed, tested and adopted by a university consortium. ERoS draws on the strengths of existing methodologies to produce an evolved model that is effective, efficient, transparent and open, capability building and sustainable. The model enables participants to communicate directly and construct peer relationships, and findings suggest this is a significant design strength. The process facilitates capability building, such that participants garnered insights valuable to enact quality assurance and enhancement of existing courses, and fosters connections that facilitate collaboration and peer-learning. ERoS successfully used open source collaborative tools to review work samples, which can be used to benchmark costed systems.